Analisis Pengaruh Pemasaran Media Sosial TikTok, Kualitas Produk, dan Kepuasan Konsumen terhadap Loyalitas Konsumen: Studi pada Konsumen Scarlett Whitening di Surabaya - Afifah Ulul Azmi; Indah Respati Kusumasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research evaluates the impact of marketing via TikTok, product quality, and customer satisfaction on customer loyalty towards Scarlett Whitening in Surabaya. In a digital context, social media has become a vital part of marketing strategy. Using a quantitative method, 100 Scarlett Whitening consumers in Surabaya were reached with a questionnaire. A nonprobability sampling method was used. Primary data obtained directly from the research object is the basis for multiple linear regression analysis to test the influence of independent variables (TikTok marketing, product quality, consumer satisfaction) on consumer loyalty. The results show the significance of the positive influence of TikTok marketing, product quality, and consumer satisfaction on customer loyalty. This research underlines the importance of integrating social media marketing strategies, especially TikTok, improving product quality, and consumer satisfaction in building customer loyalty.